Microencapsulation of tea tree oil by spray‐drying with methyl cellulose as the emulsifier and wall material together with chitosan/alginate. Issue 13 (30th November 2016) - Zhang, Song; Chen, Juan; Yin, Xueqiong; Wang, Xuyu; Qiu, Bining; Zhu, Li; Lin, Qiang
ABSTRACT: Amphiphilic methyl cellulose (MC) was used as the emulsifier and the internal wall material to increase the microencapsulation efficiency (ME) of tea tree oil (TTO) and the stability of the emulsion for spray‐drying. The results of microscopy images, zeta potential, and microencapsulation efficiency indicated that the wall material components affected the morphology, stability, and ME of the microcapsules. The microcapsules with the wall materials of MC/chitosan (CTS)/alginate (ALG) were spherical and had higher ME than those with monocomponent or bicomponents of MC, CTS, or ALG, or triple components of MC/ALG/CTS. Spray drying conditions were optimized to find the optimum microencapsulation conditions. The highest ME 89.4% and the highest oil embedding rate (ER) 90.4% were obtained through spray‐dying the emulsion of 0.8 mL TTO embraced by 0.4 g MC, 0.6 g CTS, and 3 g ALG at the drying conditions of inlet air temperature 210 °C, needling frequency 2 s, and pump flow rate 55 r/min. Microencapsulation obviously decreased the release of TTO. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44662. Abstract :